Double-Membrane Vesicles as Platforms for Viral Replication. Issue 12 (December 2020) - Wolff, Georg; Melia, Charlotte E.; Snijder, Eric J.; Bárcena, Montserrat
Abstract : Viruses, as obligate intracellular parasites, exploit cellular pathways and resources in a variety of fascinating ways. A striking example of this is the remodelling of intracellular membranes into specialized structures that support the replication of positive-sense ssRNA (+RNA) viruses infecting eukaryotes. These distinct forms of virus-induced structures include double-membrane vesicles (DMVs), found during viral infections as diverse and notorious as those of coronaviruses, enteroviruses, noroviruses, or hepatitis C virus. Our understanding of these DMVs has evolved over the past 15 years thanks to advances in imaging techniques and modern molecular biology tools. In this article, we review contemporary understanding of the biogenesis, structure, and function of virus-induced DMVs as well as the open questions posed by these intriguing structures. Highlights: Positive-sense RNA viruses utilize host membranes to generate viral replication organelles (ROs), inducing either invaginated spherules or double-membrane vesicles (DMVs) to support viral RNA synthesis. DMVs have emerged as a recurrent RO motif among important human pathogenic viruses. These include picornaviruses such as enteroviruses and poliovirus, hepatitis C virus, noroviruses, and coronaviruses such as Middle East respiratory syndrome (MERS)- and severe acute respiratory syndrome (SARS)-coronaviruses. Virus-induced DMVs appear to derive from membranes of the secretory pathway and form via several membrane remodelling steps coordinated by specific viral nonstructural proteins and host factors. Recent evidence demonstrates that DMVs are a central hub for the synthesis of viral RNA (vRNA), making them attractive targets for novel antiviral interventions.